2020
DOI: 10.3386/w28022
|View full text |Cite
|
Sign up to set email alerts
|

Learning During the COVID-19 Pandemic: It Is Not Who You Teach, but How You Teach

Abstract: We use standardized end-of-course knowledge assessments to examine student learning during the disruptions induced by the COVID-19 pandemic. Examining seven economics courses taught at four US R1 institutions, we find that students performed substantially worse, on average, in Spring 2020 when compared to Spring or Fall 2019. We find no evidence that the effect was driven by specific demographic groups. However, our results suggest that teaching methods that encourage active engagement, such as the use of smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 2 publications
2
40
1
2
Order By: Relevance
“…For example, Gonzalez et al (2020) analyzed just 458 students at 1 university. Similarly, Orlov et al (2020) observed economics students in just 7 classes across 4 universities. While the information these studies presented remains relevant to their observed samples, research that can more accurately represent larger groups of students remains crucial to policy makers.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…For example, Gonzalez et al (2020) analyzed just 458 students at 1 university. Similarly, Orlov et al (2020) observed economics students in just 7 classes across 4 universities. While the information these studies presented remains relevant to their observed samples, research that can more accurately represent larger groups of students remains crucial to policy makers.…”
Section: Discussionmentioning
confidence: 89%
“…Tomasik et al (2020) found learning progress of primary school students in Switzerland during inperson learning to be more than twice as high compared to the progress made during the eight-week school closure. Orlov et al (2020) determined that economics students at four USA universities were 0.19 SD behind. Kuhfeld et al (2020) found that Grade 3-8 students in the USA scored 5-10 percentile points below historic levels in math.…”
Section: Sample Sizementioning
confidence: 99%
“…Given the vast number of obstacles students face with remote learning, especially with the abrupt transition from COVID-19, it's not surprising that performance may have dwindled. Orlov, et al (2020) found in a study examining seven economics courses, that students performed worse during the Spring of 2020 when teaching went remote compared to the Spring or Fall of 2019. In this paper, we have the luxury of examining the same math finance undergraduate course over 6 quarters and comparing the student performance based on overall scores and team-based quiz scores.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Our findings are also pertinent to an emerging body of evidence showing that the harmful effects of school closures can be reduced through some types of school and home investments. Evidence from France, Italy and the US suggests that interactive distance learning (such as online classes) substantially reduces the negative impacts of school closures, though it is nevertheless less effective than in-person teaching (Champeaux et al, 2020;Orlov et al, 2020). These findings underline how the quality of home learning will depend on the resources and support that students have available to them, which have been found to be unevenly distributed, often along existing lines of disadvantage.…”
Section: Introductionmentioning
confidence: 99%